AB0257 Clinical Outcome of 2 Years Treatment of The Early Phase Rheumatoid Arthritis. (15th July 2016) - Sugimura, Y.; Miyamoto, S.; Kashiwagura, T.; Kobayashi, M.; Miyakoshi, N.; Shimada, Y.
Abstract : Background: Few studies have reported long term clinical outcome of patients with early phase rheumatoid arthritis (RA). Objectives: The objectives of this study were to investigate outcome of 2 years treatment for RA which was started less than 12 months after RA symptoms first appeared and to evaluate prediction factors of poorly controlled patients at 2 years. Methods: From a total of 1663 RA patients registered in the Akita Orthopedic Group on Rheumatoid Arthritis (AORA) in 2012, 66 patients were treated within the first year of RA appearance, and enrolled in this study. Sex, age, RA disease duration, Steinbroker's stage, Steinbroker's class, medications and DAS28-CRP at the baseline and 2 years post-treatment were evaluated. Furthermore, we compared the group of remission (REM) or low disease activity (LDA) with the group of medium disease activity (MDA) or high disease activity (HDA) at 2 years. Results: At the baseline, the patients included 13 males and 53 females. Mean age and RA disease duration were 59 (21–85) years and 7 (1–11) months, respectively. Fifty-four, 8, 4 and 0 patients were classified into Steinbroker's stage I, II, III, and IV, respectively. Thirty-nine, 25, 2 and 0 patients were classified into Steinbroker's class I, II, III, and IV, respectively. Thirty-seven (56%), 24 (36%), and 16 (24%) patients were treated with MTX, DMARDs, and PSL, respectively. In DAS28-CRP, 19 (29%), 13 (20%), 32 (48%), and 2 (3%) patients showed REM, LDA, MDA, and HDA, respectively. Forty-four patients were followed-up for 2 years. At 2 years, 30, 7, 5, and 2 patients were classified into Steinbroker's stage I, II, III, and IV, respectively. Thirty-one, 12, 1, and 0 patients are classified into Steinbroker's class I, II, III, and IV, respectively. In DAS28-CRP, 33 (75%), 4 (9%), 7 (16%), and 0 (0%) patients showed REM, LDA, MDA, and HDA, respectively. Compared with the group of REM or LDA, the group of MDA or HDA had significantly older age (P=0.018), higher Steinbroker's stage (P=0.012) and higher DAS28-CRP (P=0.049) at the baseline. Conclusions: At 2 years, 75% of patients with early phase RA achieved REM. Older age, higher Steinbroker's stage and higher DAS28-CRP at the baseline could be prediction factors of poorly controlled patients at 2 years. Acknowledgement: We wish to thank the members of AORA. Disclosure of Interest: None declared